Combination of seed priming and nutrient foliar application improved physiological attributes, grain yield, and biofortification of rainfed wheat - Moradi, Layegh; Siosemardeh, Adel (Frontiers in Plant Science, 2023)
Seed priming and foliar application are two crop management practices that can increase grain yield and quality. The research aimed to assess the influence of seed priming and foliar application on rainfed wheat. Two field experiments with two seed priming rates (control and priming) and five foliar applications [control, urea (4%), silicon (4 mM), FeSO4.7H2O (0.6%), and ZnSO4.7H2O (0.4%)] at the anthesis/Z61 stage were conducted. Seeds were primed for 12 h at 25 ± 2°C, by soaking in an aerating solution [urea (20 g L−1) + FeSO4.7H2O (50 ppm) + ZnSO4.7H2O (50 ppm) + silicon (20 mg L−1)]. Seed weight-to-solution volume ratio was 1:5 (kg L−1). A pot experiment was also conducted to examine the effect of priming on root growth. Overall, combined seed priming and foliar application induced a positive impact on physiological traits and attributes. Maximum chlorophyll a, chlorophyll b, total chlorophyll, and carotenoid concentrations (1.58, 0.669, 2.24, and 0.61 mg g−1 FW), membrane stability index (77.31%), superoxide dismutase and peroxidase activity (0.174 and 0.375 Unit mg−1 protein), 1,000-grain weight (35.30 g), biological yield, grain yield (8,061 and 2,456 kg ha−1), and minimum malondialdehyde concentration (3.91 µg g−1 FW) were observed in seed priming combination with ZnSO4 foliar application. The highest glycine betaine concentration (6.90 mg g−1 DW) and proline (972.8 µg g−1 FW) were recorded with the co-application of seed priming and foliar urea spraying. Foliar application of ZnSO4, FeSO4, and urea drastically enhanced grain Zn (29.17%), Fe (19.51%), and protein content (increased from 11.14% in control to 12.46% in urea foliar application), respectively. Compared to control, seed priming increased root length, root volume, and dry mass root by 8.95%, 4.31%, and 9.64%, respectively. It is concluded that adequate Zn, Fe, silicon, and N supply through seed priming and foliar applications of these compounds at the terminal stage of rainfed wheat alleviates drought stress and improves GY and biofortification.